Challenges of the European Union social market economy in the human resource management paradigm - Lobanova, Liudmila (Business: Theory and Practice, 2014)
Peculiarities  of  European  human  resource  management  models  are  determined  by  the  specifics  of  EU  integration,  development and enlargement processes that are centred on implementation of the social model in the development of the social market economy in the European continent under conditions of intensified cohesion processes. The article reveals the impact of the changing environmen and factors determining the transformation of human resource management models on historic evolution of approches to management of people. In addition, it determines links between transformation of human resource management models and the EU development stages as well as proposes guidelines for the development of promising socially centred human resource management models in response to challenges faced by the European social model under the conditions of cohesion processes. The conceptual study is performed using literature analysis and synthesis, theoretical modelling, metaanalysis and interpretation techniques. Insights were drafted using the systemic holistic approach and graphic modelling.Europos Sąjungos socialinės rinkos ekonomikos iššūkiai žmogiškųjų išteklių vadybos paradigmaiSantraukaŽmogiškųjų išteklių vadybos modelių specifiką Europoje nulemia Europos integracijos bei Europos Sąjungos raidos ir plėtros procesai, orientuojami į socialinio modelio koncepcijos įgyvendinimą kuriant Europos kontinente socialinę rinkos ekonomiką intensyvėjančių sanglaudos procesų sąlygomis. Straipsnyje atskleidžiama žmogiškųjų išteklių vadybos modelių transformacijas lemiančių aplinkybių ir aplinkos pokyčių įtaka istoriniam požiūrių į žmonių valdymą evoliucionavimui, nustatomos žmogiškųjų išteklių vadybos modelių kaitos sąsajos su Europos Sąjungos raidos ir plėtros etapais, siūlomos perspektyvių socialiai orientuotų žmogiškųjų išteklių vadybos modelių plėtotės gairės, reaguojant į Europos socialinio modelio iššūkius sanglaudos procesų sąlygomis. Konceptualus tyrimas atliekamas taikant mokslinės literatūros analizės ir sintezės, teorinio modeliavimo, metaanalizės ir interpretavimo metodus, o įžvalgoms parengti pasitelktas sisteminis holistinis požiūris ir grafinio modeliavimo metodas.Reikšminiai žodžiai: žmogiškųjų išteklių vadyba, socialinis modelis, socialinė rinkos ekonomika, socialinės kokybės modelis, sanglaudos procesai.